A new species of freshwater leech of the genus Haementeria (Annelida: Glossiphoniidae) from Jalisco State, Mexico - Oceguera-Figueroa, Alejandro (Zootaxa, 2006)
Haementeria lopezi n. sp. is described based on the examination of 11 specimens collected in northern Jalisco state, Mexico. Leeches were found feeding on blood of Bufo marinus (Bufonidae) and Smilisca baudinii (Hylidae). Diagnostic characters are: undivided annuli and absence of conspicuous papillae on dorsal surface. Specimens measure 22–59 mm length and 6-9 mm wide.